Perubahan Siklus Estrus Akibat Induksi Peningkatan Kadar Prostaglandin F2α (PGF2α) Pada Fase Luteal Kambing Peranakan Boer - Aries Erlinda Ratna Wardhani; Agung Pramana W.M (Biotropika: Journal of Tropical Biology, 2014)
ABSTRACT The objective of this study to understand the effect of PGF2α injection in early diestrus phase and mid- diestrus to the estrous cycle. Treatment in this study are early diestrus control, mid- diestrus control, administration of PGF2α on early diestrus phase and administration of PGF2α in mid diestrus phase (each group n=3.) 1.5 ml Capriglandin® was injected once intramusculary. Then, phase change observed every day start one day since injection. Estrous phase were determined by observation vaginal smear cytology. Data were analyzed by Mann- Whitney method using Microsoft Excel software and SPSS 16.0 for Windows. There’s no significant difference in diestrus and proestrus length on injected group at early diestrus and control early diestrus group, onset estrous of injected group and control group respectively on day 15 and on day 16. The injected group at mid diestrus and control mid diestrus group have a significant difference at onset estrous and diestrus length but there is no significant difference in proestrus length, onset of estrous in the injection group and control group respectively on day 6.7 and on day 12 day (P < 0.05). It can be concluded that there is no response of single injection of PGF2α when injected at early diestrus, but when injected at mid- diestrus causes a shorter diestrus phase than the control respectively 2,3 and 8 days. Keywords : PGF2α, onset of estrous, estrous synchronization, vaginal smears